Low velocity impact response and damage of laminate composite glass fibre/epoxy based tri-block copolymer. (July 2015) - Matadi Boumbimba, R.; Froustey, C.; Viot, P.; Gerard, P.
Abstract: Two types of laminate composites made of glass fibre/epoxy matrix (EPO_FV) and glass fibre/epoxy modified tri-block copolymer (Nanostrength) matrix (EPONS_FV) were manufactured by compression moulding. Some AFM investigations have been done to identify the Nanostrength dispersion in the epoxy matrix and some DMA analyses have been performed, at different frequencies, to understand the frequency or the strain rate sensitivity of both composites. Compared to EPO_FV, EPONS_FV exhibits a significant frequency/strain rate sensitivity. Impact resistance of the composite was investigated by means of low velocity impact tests. The low velocity impact results indicate that the addition of Nanostrength leads to the improved impact resistance and an increase in absorbed energy, especially at high impact energy level. SEM observations, performed on ion polished samples, reveal the presence of micro-cracks for both composites. Micro-cracks consist of a coalescence of fibre matrix de-bonding. It was also observed that EPONS_FV contains a lower density of micro-cracks compared to EPO_FV, confirming the fact that the composite with Nanostrength absorbs more energy by Nanostrength micelles cavitation.